2011
DOI: 10.1209/0295-5075/96/60013
|View full text |Cite
|
Sign up to set email alerts
|

Loss of synchronization in complex neuronal networks with delay

Abstract: We investigate the stability of synchronization in networks of delay-coupled excitable neural oscillators. On the basis of the master stability function formalism, we demonstrate that synchronization is always stable for excitatory coupling independently of the delay and coupling strength. Superimposing inhibitory links randomly on top of a regular ring of excitatory coupling, which yields a small-world-like network topology, we find a phase transition to desynchronization as the probability of inhibitory link… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 36 publications
(27 reference statements)
5
59
0
Order By: Relevance
“…Time delays are always present in coupled systems due to the finite signal propagation time. These time lags give rise to complex dynamics and have been shown to play a key role in the synchronization behavior of systems [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], see also the review [43]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Time delays are always present in coupled systems due to the finite signal propagation time. These time lags give rise to complex dynamics and have been shown to play a key role in the synchronization behavior of systems [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], see also the review [43]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In [Lehnert, 2010;Lehnert et al, 2011a], it was shown that the MSF for all values of K and τ shows qualitatively the same behavior. In particular, the stable region is in very good approximation given by the unit cycle.…”
Section: Type-ii Excitabilitymentioning
confidence: 97%
“…In the last two decades dynamics on network received a growing amount of interest [Dhamala et al, 2004;Zigzag et al, 2009;Choe et al, 2010;Chavez et al, 2005;Sorrentino and Ott, 2007;Albert et al, 2000;Kinzel et al, 2009;Lehnert et al, 2011a;Keane et al, 2012]. One of the central topics of dynamics on networks is synchronization [Strogatz and Stewart, 1993;Rosenblum et al, 1996;Pikovsky et al, 2001;Pecora and Carroll, 1998;Mosekilde et al, 2002;Wang and Chen, 2002;Arenas et al, 2006aArenas et al, , 2008Balanov et al, 2009;Omelchenko et al, 2010;Schöll, 2013].…”
Section: Dynamics On Networkmentioning
confidence: 99%
See 2 more Smart Citations